The Environmental Impacts of Copper Mining During the Swansea Moment in the 19th Century - Morrisey, Katherine (Revista de Historia Social y de las Mentalidades, 2017)
This paper examines 19th century copper mining’s environmental impacts during the “swansea moment” the global industrial diaspora centered on welsh smelting technology and british capital between the late 1820s and the 1870s. Drawing on the perspective of environmental history, examples from Chile, Cuba and Australia, and recent historiography, it raises questions about ecological, social and cultural changes in mining landscapes and beyond, at the local, regional and global scales. It argues for the necessity to consider the interconnections of material and mental environmental changes in evaluating the broad range of human-nature relations.